Embedded AlN/GaN multi-layer for enhanced crystal quality and surface morphology of semi-polar (11-22) GaN on m-plane sapphire - Omar, Al-Zuhairi; Shuhaimi, Ahmad; Makinudin, Abdullah Haaziq Ahmad; Abdul Khudus, Muhammad Imran Mustafa; Supangat, Azzuliani (Elsevier, 2018)
We demonstrate high quality semi-polar (11-22) gallium nitride thin film grown on m-plane sapphire substrate with the insertion of AlN/GaN multi-layer via MOCVD. The influence of three different number of multi-layers AlN/GaN pairs on the crystal quality and surface morphology of semi-polar (11-22) gallium nitride thin film is investigated. The surface morphology analysis strongly suggests that increasing the number of AlN/GaN pairs from 20 to 60 suppresses the arrowhead-like and undulated features. The increase of AlN/GaN pairs also enhanced the surface quality, with the root mean square roughness improving from 16.24 nm to 6.08 nm. The abruptness of the interface between the AlN/GaN pairs was seen to improve significantly upon reaching the 40th pair where a continuous thin layer was clearly observed for each pair. The crystal quality was also observed to be enhanced at higher number of AlN/GaN pairs, where the on- and off-axis X-ray rocking curve showed significant reduction in the full width at half maximum of at least ~10% and 20%. Finally, x-ray reciprocal space mapping analysis further confirms the enhancement of the crystal quality as the diffuse scattering streak was suppressed, which may indicate a significant reduction of the defect density.